Structural Modifications for Biological Activity Enhancements in Thiosemicarbazone Scaffolds and Their Metal Complexes - Khan, Tahmeena; Raza, Saman; Hashmi, Kulsum; Ahmad, Mohammad Imran; Khan, Abdul Rahman (Synlett, 2025)
The molecular weight of a typical small molecule drug is usually less than 500 Da. Small molecules can influence the function of different proteins by interacting with their targets and forming complexes. Thiosemicarbazones (TSCs) are biologically important Schiff base ligands. Due to their considerable biological importance, they have been explored for an extended period. TSC complexes exhibit structural diversity, varied bonding patterns, and hold promise for their biological importance, as well as ion-sensing properties. This review explores the medicinal applications of TSC complexes and the effect of different factors like molecular weight, structural alterations, presence of benzene ring and electron-donating and -withdrawing groups in the TSC moiety. Molecules in compliance with Lipinski’s rule have enhanced activity. Complexes with low molecular weight also possessed better absorption, distribution, metabolism, and excretion (ADME) characteristics, and good to moderate bioactivity scores. Mixed-ligand complexes have also been discussed, showing that synergetic effect may enhance the overall stability of the complex. Small molecules can be utilized as medicinal agents and as chemical probes for the exploration of new drug targets and through structural biology crucial interactions between the molecules and drug targets can be comprehended, thereby propelling target-based drug discovery.1 Introduction: Small Therapeutic Molecules2 TSCs as Potent Schiff Bases2.1 Biological Activity of TSCs and Their Complexes2.1.1 Anticancer Properties2.1.2 Antibacterial Activity2.1.3 Antiviral Activity2.1.4 Antimalarial Activity2.1.5 Antifungal Activity3 Biological Activity: Factors of Consideration3.1 Molecular Weight3.2 Structural Alterations3.3 Presence of Aromatic Rings and Electron-Donating or -Withdrawing Groups4 Mixing and Permutations of Ligands5 Mechanistic Insights6 Activity of Hybrid TSCs7 Future Prospects7.1 Structure-Activity Relation (SAR) Studies7.2 Donor Atoms and Chelation7.3 Metal Ion Coordination7.4 Factors Affecting Biological Activity7.5 Pharmacokinetic Profiling8 Conclusion
Keywords: human health; medicine; Schiff bases; thiosemicarbazones; Lipinski’s rule